S115 Hot-hmv uk trial secondary outcome analysis: early readmission is reduced by the addition of home mechanical ventilation to home oxygen therapy in copd patients with chronic respiratory failure following a life-threatening exacerbation. (15th November 2016) - Murphy, PB; Arbane, G; Bourke, S; Calverley, P; Crooks, A; Dowson, L; Duffy, N; Gibson, GJ; Hughes, P; Hurst, JR; Lewis, K; Mukherjee, R; et al.
Abstract : Introduction: Hospital readmission following treatment for a life-threatening exacerbation of COPD with acute NIV is frequent and associated with an adverse impact in terms of lung function and health related quality of life. They have been identified as a priority area in the NHS with financial penalties for any patient readmitted within 28 days following discharge. Method: A multicentre open labelled randomised controlled trial recruited patients with persistent hypercapnia (PaCO 2 > 7 kPa) 2–4 weeks following resolution of acute acidosis. Patients were randomised to either home oxygen therapy (HOT) or HOT and home mechanical ventilation (HOT-HMV). HMV was titrated overnight to control nocturnal hypercapnia. Follow up was for 12 months. The primary outcome, 12-month admission free survival, has been reported previously demonstrating a significant treatment effect (ERS 2016). Secondary outcome analysis included 28-day all-cause hospital readmission and 12 month exacerbation rate. Results: 116 patients were randomised (HOT = 59, HOT-HMV = 57), age 67 ± 10 years, FEV1 0.6 ± 0.2 L, PaCO 2 7.9 ± 0.9 kPa. 28-day readmission was 22 (37%) in the HOT and 7 (12%) in the HOT-HMV arm (unadjusted HR 0.27, 0.12 to 0.63, p = 0.003; adjusted HR 0.26, 0.11 to 0.61, p = 0.002) (Figure 1 ). 12 month exacerbation rate was reduced from median 5 (1 to 9) per year in the HOT arm to 4 (2to 6) in the HOT-HMV arm (unadjusted HR 0.64 (0.44 to 0.94); p = 0.022; adjusted HR 0.66, 0.46 to 0.95, p = 0.026). Conclusion: The addition of HMV to HOT in patients with persistent hypercapnia following an acute life-threatening exacerbation of COPD reduces both 28-day readmission and 12 month exacerbation frequency. These data strongly support a change in clinical practice in the management of patients with severe COPD and persistent hypercapnia.